2021
DOI: 10.1038/s41467-021-26066-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling alpha-synuclein pathology in a human brain-chip to assess blood-brain barrier disruption

Abstract: Parkinson’s disease and related synucleinopathies are characterized by the abnormal accumulation of alpha-synuclein aggregates, loss of dopaminergic neurons, and gliosis of the substantia nigra. Although clinical evidence and in vitro studies indicate disruption of the Blood-Brain Barrier in Parkinson’s disease, the mechanisms mediating the endothelial dysfunction is not well understood. Here we leveraged the Organs-on-Chips technology to develop a human Brain-Chip representative of the substantia nigra area o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 97 publications
6
104
0
1
Order By: Relevance
“…By leveraging next-generation sequencing data and information retrieved from wellcurated databases providing signature gene sets characteristic for the human cortex, we were able to show that the Brain-Chip exhibits higher transcriptomic similarity to the adult cortical tissue than the transwells, both models with the same cellular composition. These data complement previous reports on the advantages of the microfluidic organ-chip systems to provide a better tissue-relevant microenvironment compared to other commonly used conventional culture systems (Pediaditakis et al, 2021;Sances et al, 2018). Most importantly, our findings demonstrate the closeness of the Brain-Chip to the adult human cortex tissue and the cells' maturation state after seven days in culture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By leveraging next-generation sequencing data and information retrieved from wellcurated databases providing signature gene sets characteristic for the human cortex, we were able to show that the Brain-Chip exhibits higher transcriptomic similarity to the adult cortical tissue than the transwells, both models with the same cellular composition. These data complement previous reports on the advantages of the microfluidic organ-chip systems to provide a better tissue-relevant microenvironment compared to other commonly used conventional culture systems (Pediaditakis et al, 2021;Sances et al, 2018). Most importantly, our findings demonstrate the closeness of the Brain-Chip to the adult human cortex tissue and the cells' maturation state after seven days in culture.…”
Section: Discussionsupporting
confidence: 89%
“…Morphological Analysis. Immunocytochemistry was conducted as previously described (Pediaditakis et al, 2021). Cells were blocked on the Brain-Chip in phosphate-buffered saline (PBS) containing 10% donkey serum (Sigma) at 4°C overnight.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson disease is a disorder of the substantia nigra region of the brain that is characterized by abnormal accumulation of α-synuclein aggregates, loss of dopaminergic neurons and proliferation of glial cells. A two-channel human brain chip representative of this region was created containing iPS-cell-derived dopaminergic neurons, astrocytes, microglia and pericytes interfaced with iPS cell-derived microvascular brain endothelium 84 . Transcriptomic analysis revealed that gene expression levels on-chip were much closer to those seen in the mature adult substantia nigra than in conventional culture systems.…”
Section: Clinical Mimicry In Organ Chipsmentioning
confidence: 99%
“…Another example comes from PD where neurodegeneration is driven by progressive dysfunction of dopaminergic neurons in the substantia nigra -an area projecting to the cerebral cortex which was targeted by FUS+MB opening in a PD clinical trial [111] and in rat brain [112]. Recently, Pediaditakis et al developed a novel substantia-nigra human Brain-Chip in vitro model containing dopaminergic neurons, astrocytes, microglia, pericytes, and BMEC that could serve as a testing platform for validation of new drugs for PD [113]. Such multicellular brain-region specific BBB models, when combined with FUS+MB in vitro system, could become useful predictors of FUS-mediated therapeutic uptake in diseaseassociated brain structures.…”
Section: Human In Vitro Bbb Models Can Bridge the Gap Between Fus-med...mentioning
confidence: 99%